The Brazilian Holepyris (Hymenoptera, Bethylidae), with description of a new species from Amazonian forest. Zootaxa, 1357, 61–68. (ERRATUM)The Brazilian Holepyris (Hymenoptera, Bethylidae), with description of a new species from Amazonian forest. Zootaxa, 1357, 61–68. - Gobbi, F.t.; Azevedo, C.o. (Zootaxa, 2007)
ERRATUM